HIV is always with me: men living with perinatally acquired HIV and planning their families - Echenique MI; Bookman RS; Rodriguez VJ; LaCabe RP; Potter JE; Jones DL (Dove Medical Press, 2017)
Marisa I Echenique,1 Rachel S Bookman,1 Violeta J Rodriguez,1 Richard P LaCabe,1 JoNell Efantis Potter,2 Deborah L Jones1 1Department of Psychiatry and Behavioral Sciences, 2Department of Obstetrics and Gynecology, University of Miami Miller School of Medicine, Miami, FL, USA Abstract: Once expected to not survive childhood, youth with perinatally acquired HIV (YPHIV) have now reached young adulthood and are of reproductive age and sexually active. Given the health impact of pregnancy among YPHIV, understanding reproductive decision making may inform preconception counseling strategies. Most literature regarding reproductive health among YPHIV focuses on women, overlooking one of the most important factors influencing the reproductive decision-making process, male sexual partners. This study examined attitudes, perceptions, and experiences of young men with perinatally acquired HIV (YMPHIV) regarding family planning and relationships, safer sex, disclosure, stigma, and psychological health. Participants (n=21) were YMPHIV aged 18–24 years recruited in Miami, Florida. Focus groups (n=4) were conducted; qualitative data were analyzed using grounded theory. HIV disclosure, stigma, fertility intentions, safer preconception knowledge, attitudes and practices, family planning communication with medical providers and family, and mental health emerged as themes. Results suggest that despite accurate knowledge regarding healthy preconception practices, psychopathology, substance use, and stigma impact the uptake of HIV health care interventions. Effective interventions on preconception counseling may require more tailored approaches than knowledge-based psychoeducation alone, such as inclusion of psychological treatment, which could be offered in HIV health care settings to optimize health outcomes. Keywords: preconception counseling, fertility decision making, young adults, HIV risk reduction, HIV knowledge